2013
DOI: 10.1186/1471-2180-13-54
|View full text |Cite
|
Sign up to set email alerts
|

Advanced application of bovine intestinal epithelial cell line for evaluating regulatory effect of lactobacilli against heat-killed enterotoxigenic Escherichia coli-mediated inflammation

Abstract: BackgroundPreviously, a bovine intestinal epithelial cell line (BIE cells) was successfully established. This work hypothesized that BIE cells are useful in vitro model system for the study of interactions of microbial- or pathogen-associated molecular patterns (MAMPs or PAMPs) with bovine intestinal epithelial cells and for the selection of immunoregulatory lactic acid bacteria (LAB).ResultsAll toll-like receptor (TLR) genes were expressed in BIE cells, being TLR4 one of the most strongly expressed. We demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 34 publications
(55 reference statements)
5
46
2
Order By: Relevance
“…The TLR-2 and TLR-4 activation and expression by LPS (pathogens) is known as one of the most important mechanisms by which the immune system controls reactions to bacteria in particular in the activation phase, therefore, over-expression of TLR-2 and TLR-4 during any bacterial infection could cause an elevated inflammatory response in the body. While early activation of TLRs expression is reported in response to bacterial LPS from pathogenic Salmonella typhimurium [61] as well as E. coli infection in bovine intestinal epithelial cells [66], our results show tolerance as a result of co-culturing PBMC with S. thermophilus 285 by down regulation of TLRs genes. Downregulated mRNA expression of TLRs genes, specifically TLR-1, TLR-2, TLR-4 and TLR-8 indicates anti-inflammatory characteristics for S. thermophilus 285.…”
Section: S Thermophilus 285 Downregulates Mrna Expression Levels Of contrasting
confidence: 63%
“…The TLR-2 and TLR-4 activation and expression by LPS (pathogens) is known as one of the most important mechanisms by which the immune system controls reactions to bacteria in particular in the activation phase, therefore, over-expression of TLR-2 and TLR-4 during any bacterial infection could cause an elevated inflammatory response in the body. While early activation of TLRs expression is reported in response to bacterial LPS from pathogenic Salmonella typhimurium [61] as well as E. coli infection in bovine intestinal epithelial cells [66], our results show tolerance as a result of co-culturing PBMC with S. thermophilus 285 by down regulation of TLRs genes. Downregulated mRNA expression of TLRs genes, specifically TLR-1, TLR-2, TLR-4 and TLR-8 indicates anti-inflammatory characteristics for S. thermophilus 285.…”
Section: S Thermophilus 285 Downregulates Mrna Expression Levels Of contrasting
confidence: 63%
“…Less clear is whether the negative regulators are the targets of pathogen infection. For instance, IRAK-M was up-regulated in LPS treated macrophages or in lung epithelial cells in response to S. pneumonia [50], [55], while ETEC infection did not modify IRAK-M and Tollip expression in bovine epithelial cells, and S. typhi caused a decrease in Tollip level in dendritic cells [26], [56]. Our results show a decrease in Tollip and IRAK-M levels triggered by ETEC infection in Caco-2/TC7 cells, whereas these negative regulators are unaffected by ETEC in intestinal explants.…”
Section: Discussionmentioning
confidence: 99%
“…The SISP model also allowed determination of the early gene expression response of the pig small intestinal mucosa to infection with ETEC (28) and Salmonella (29). Most studies employing SISP, however, focused on analysis of physiological and immune responses of the host, including fluid loss, electrolyte secretion, and the expression of cytokines (23,26,27,30). Very few studies provided a detailed bacteriological analysis of the model; previous studies using the SISP model reported only cell counts of ETEC in the lumen (27,31,32).…”
Section: Discussionmentioning
confidence: 99%